The Dickens Universe: Gazing at the Heavens - Dominic RAINSFORD (E-REA)
Stars and other astronomical references play a significant part in Charles Dickens’s writings, from the 1830s to the end of his career. He took an interest in contemporary discoveries and theories in astronomy, but also uses cosmic phenomena in religiously inspired and symbolic ways. This network of references, from the farcical depiction of an astronomer in The Lamplighter and the self-aggrandising cosmic references of Mr. Pecksniff, through the benevolent star that shines in Hard Times and brief remarks on arguments for and against life on other planets, culminates in, and gives extra meaning to, Dickens’s greatest work of stargazing, Great Expectations.